Ballroom Dance and Body Size Perception. Issue 2 (October 2014) - Fonseca, Cristiane Costa; Thurm, Bianca Elisabeth; Vecchi, Rodrigo Luiz; Gama, Eliane Florencio
Ballroom dancing consists in the performance of rhythmic movements guided by music, which provide sensorimotor integration and stimulate feelings. The body schema is the unconscious sensorimotor representation that allows the individual to perceive his anatomical body in space. Comprising tactile, proprioceptive, kinesthetic, and environmental information, it is directly related to movement. The aim of this study was to investigate the influence of non-competitive practice of ballroom dancing on body perception. The projection point test was applied to 30 volunteers before and after a period of 3 mo.; 15 controls attended lectures on body perception and 15 participants took dance lessons. It was observed that ballroom dancing brought perceptual benefits for those who practiced it.